Máquinas térmicas: uma proposta para o ensino das leis da termodinâmica para o ensino médio - Saraiva, Raysa Zurra (2016)
This thesis describes a didactic proposal used to aid teacher and students in the construction of concepts necessary for understanding the Thermodynamic laws, such as pressure, volume, heat, work and temperature. For its development was first carried out an analysis of textbooks present in PNLD-2012 using elements of Chevallard’s didactic transposition, and as a theoretical basis for the creation and organization of all activities employ socio-historical theory of Vygotsky. These procedures consisted in investigative activities, experimental and traditional, like the resolution of exercises. The generated products consist of a guide for the teacher, in which he will find not only the activities of didactic sequence that we propose for learning these laws, but also suggestions on how to organize the dynamics in the classroom and how to proceed as mediator for conducting such activities. In addition, is presented an Stirling engine, made with reusable materials, used in construction of the P-V diagram of the Stirling cycle.